Clinical features and outcomes of influenza infections in lung transplant recipients: a single‐season cohort study. Issue 3 (9th May 2014) - Schuurmans, M.M.; Isenring, B.D.; Jungo, C.; Boeni, J.; Mueller, N.J.; Kohler, M.; Benden, C.
Abstract Background For lung transplant recipients (LTRs) influenza infections pose a considerable risk for complications. These infections have mainly been described in hospitalized patients. The aim of this study was to describe characteristics of predominantly outpatient‐treated influenza infections. Methods We conducted a single‐season (2010/2011) retrospective observational study using database information of our cohort. Patients with evidence for respiratory tract infection received empirical oseltamivir and an oral antibiotic, pending results from nasopharyngeal swab analysis. In laboratory‐confirmed influenza infection, treatment was continued and serial weekly swabs were performed until virologic results were negative. Results We identified 22 infections in 21 of 173 patients followed up; influenza A virus was diagnosed in 13 and influenza B virus in 9 infections. Leading presenting symptoms were cough and rhinorrhea. Oseltamivir was given within 48 h of symptom onset in 13 infections and within 72 h in 21 infections. Prolonged viral shedding (PVS) for ≥7 days was detected in 15 infections; median shedding duration for influenza A was 21 days. In univariable analysis, viral load (VL) at diagnosis was associated with extended duration of shedding (P = 0.006). Multivariable analysis confirmed this association. Bronchiolitis obliterans syndrome stage increased in 3 patients at 6‐month follow‐up. Conclusion In this study, PVS of influenza virus was detected in the majority of LTRs and high VL at diagnosis was predictive for prolonged shedding, which occurred despite extended antiviral therapy.